Organs-without-body: a study on the genealogy of vision leading to the posthuman age - Feng Hong (Humanities & Social Sciences Communications)
Abstract In 1834, an American medical missionary, Peter Parker, arrived in Guangdong and established a hospital. He used his medical skills to evangelise and commissioned a local artist named Lam Qua to paint numerous medical portraits. Previous studies on these portraits have mainly focused on historiography or critical discourse studies, with little attention given to the visual thinking behind them. Therefore, this paper uses Foucault’s archaeology of knowledge to systematically sort out similar images from different periods to demonstrate how the epistemological type brought by medical observation operates and is represented through discursive formation. The study shows that Lam Qua’s medical portraits can be traced back to clinicians’ records of cases and served as ethnographic displays, similar to freak shows. Information gradually becomes emphasised partially due to its detachment from the entity in the dissemination process. This idea inspired Rei Kawakubo’s clothing fashions, while Cunningham’s dance art takes it further by abstracting information from the body, visually representing posthuman thinking. These seemingly unrelated cases belong to the same collection of statements that form a system called organs-without-body in this paper, serving as a metaphor for non-physical information to help us better understand the formation of posthuman thought.